Cardiac rehabilitation and adverse events among adult patients with simple congenital heart disease and heart failure - Benjamin JR Buckley; Thijs P. Kerstens; Madeleine France-Ratcliffe; Gregory Y.H. Lip; Dick HJ Thijssen (Elsevier, 2024)
Aims: Improved care has resulted in prolonged survival of patients with congenital heart disease (ConHD), increasing age-related cardiovascular comorbidities. Although cardiovascular rehabilitation (CR) represents evidence-based care for heart failure (HF), the clinical impact of CR in patients with ConHD who developed HF during adulthood is unclear. We investigated 12-month mortality and morbidity in patients with simple ConHD diagnosed with HF with CR versus without CR. Methods: A retrospective cohort study was conducted for the time period February 2004 - February 2024. Utilizing TriNetX, a global federated health research network, a real-world dataset of simple ConHD patients was acquired to compare patients with vs. without (controls) prescription for exercise-based CR. Patients were propensity-score matched for age, sex, ethnicity, comorbidities, procedures, and medication. The primary outcome was a composite of all-cause mortality, ischemic stroke, and acute coronary syndrome (major adverse cardiovascular events; MACE) within 12 months. Results: Following propensity score matching, the total cohort consisted of 6,866 simple ConHD patients with HF. CR was associated with significantly lower odds for MACE (odds ratio (OR) 0.61 [95 % confidence interval (CI): 0.54-0.69]) and its individual components all-cause mortality (OR 0.40 [95 % CI 0.33-0.47]) and ischemic stroke (OR 0.75 [95 % CI 0.64-0.88]), but not acute coronary syndrome (OR 1.24 [95 % CI 0.91-1.69]). Conclusion: CR was associated with significantly lower 12-month MACE in patients with simple ConHD with concomitant HF compared to usual care.